The palm oil import demand in selected European countries: a cointegration analysis - Hameed, Amna Awad Abdel; Mohamed Arshad, Fatimah (School of Social Sciences, Universiti Sains Malaysia, 2012)
This paper examines the palm oil import demand in European countries, specifically, Austria, France, Germany, Italy, Spain and the United Kingdom with a special focus on the impact of biodiesel development in these countries. The paper uses annual data to investigate the palm oil import demand in selected European countries, namely, Austria, France, Germany, Italy, Spain, and the United Kingdom; jointly, accounting for more than 70% of the biodiesel production in EU27. Six single equation models are specified to represent palm oil import demand functions in those countries. The models have been estimated using the augmented autoregressive distributed lag (ARDL) technique. The findings of the study reveal that rapeseed and sunflower oils are the main substitutes for the palm oil in Europe. The palm oil price came out to be a major determinant of palm oil demand across the six models. It is also found that the industrial production index is an important factor affecting the demand in the all studied countries. The palm oil import demand in Austria, UK, and Germany is significantly, influenced by the start of the commercial production of biodiesel whilst the demand in France, and Spain was boosted by the introduction of the EU’s directive on the promotion of the use of bio-fuels for transport. However, neither of them produced a significant impact on the demand in Italy that is significantly affected by the development in technology represented by an upward trend.